Entrepreneur's Commitment to Achieve Success - Apriyanti, Masayu Endang; Astuty, Pudji (Future Science / FSH-PH Publications, 2023)
Entrepreneurs are noble jobs because they provide many benefits to others, help the government reduce unemployment and alleviate poverty, which in turn can improve people's welfare. However, not everyone wants and is able to become an entrepreneur, because to become a true entrepreneur, it is not only seeking profit for oneself, but also thinking about the good and benefits for many parties which is carried out wholeheartedly, by dedicating the best in every endeavor it undertakes. This study analyzes secondary data, from articles, books, scientific journals and primary data through direct interviews with Mr. Alex Wijaya, as an entrepreneur at PT. Cpta Medya Filter, from this informants who are in accordance with their expertise in a field, so that those concerned can be used as resource persons to be used as objects of research, regarding the commitment of entrepreneurs in starting and operating their businesses to achieve success. The research findings show that the strong commitment of employers plays an important role in supporting the achievement of goals. a business that was founded 20 years ago, its credibility is getting better day by day, as evidenced by its effective business management, so that operations run smoothly and the business economy is getting better. even affected by the pandemic for about 2 years, demand has decreased and operations have stalled, but all can be overcome, able to survive and even have more assets for the welfare of the company and all employees.